Alcohol management practices in community football clubs: Association with risky drinking at the club and overall hazardous alcohol consumption. (29th October 2014) - Rowland, Bosco; Tindall, Jenny; Wolfenden, Luke; Gillham, Karen; Ramsden, Robyn; Wiggers, John
Abstract Introduction and Aims Across the world, it has been estimated that approximately 270 million people participate in community football clubs. However, the community sports club setting is associated with high levels of risky alcohol consumption. The study examined if sporting club alcohol management practices are associated with risky consumption of alcohol by club members while at the club, and also whether such consumption is directly and indirectly associated with club member overall hazardous alcohol consumption. Design and Methods Telephone surveys were conducted with a representative from 72 community football clubs in New South Wales, Australia, and 1428 club members. A path and mediation analysis was undertaken to determine the association between 11 club alcohol management practices and member alcohol consumption, at the club and overall hazardous consumption. Results Three alcohol management practices were associated with an increased probability of risky drinking while at the club: having alcohol promotions; serving intoxicated patrons; and having bar open longer than 4 h. A mediation analyses identified that risky drinking at the club as a result of these three practices was also linked to increase risk in being an overall hazardous drinker. Discussion and Conclusion Modifying alcohol management practices in community football clubs has the potential to reduce both risky alcohol consumption by members in this setting and the prevalence of overall hazardous alcohol consumption. Coordinated, multi‐strategic interventions are required to support community football clubs to modify their alcohol management practices and hence contribute to reducing the burden of alcohol‐related harm in the community. [Rowland B, Wolfenden L, Tindall J, Gillham K, Ramsden R, Wiggers J. Alcohol management practices in community football clubs: Association with risky drinking at the club and overall hazardous alcohol consumption. Drug Alcohol Rev 2015;34:438–446]